Characteristics of Invasive Pulmonary Fungal Diseases Diagnosed by Pathological Examination. (28th October 2021) - Zhang, Dong; Li, Xin; Zhang, Junquan; Wu, Junping; Sun, Xin
Abstract : Objective . To explore the characteristics of invasive pulmonary fungal disease and the spectrum of pathogens causing invasive pulmonary fungal disease diagnosed by pathological examination using fungal stains. Methods . Patients with an invasive pulmonary fungal disease diagnosed by histopathological analysis through the use of fungal stains (including Grocott's methenamine silver and periodic acid-Schiff stains) were included in this study. The clinical records, radiological reports, pathology, and fungal culture results were reviewed. Results . Forty-eight invasive pulmonary fungal disease patients diagnosed by histopathological analysis in the Tianjin Haihe Hospital (including 8 cases obtained by pulmonary resection, 35 cases by fiberoptic bronchoscopic biopsy, and 5 cases by percutaneous lung biopsy) were included. There were 24 male and 24 female patients, aged 21–80 years (53 ± 13 years). There were 37 cases of pulmonary aspergillosis, 4 cases of pulmonary cryptococcosis, 2 cases of pulmonary mucormycosis, and 5 in which pathogens were not determined due to limited tissue availability. Among 48 cases, 32 specimens were submitted to fungal culture. No fungus was detected in culture, although 26 cases of fungus infections were diagnosed by histopathological analysis. Only 3 cases were consistent between histopathological and culture results. In 3 cases, the pathogen was identified as Aspergillus spp. by the histopathological analysis, while the contrasting fungal culture results identified Candida albicans . Conclusion . Candida albicans pneumonia was rare, while aspergillosis was common in invasive pulmonary fungal disease diagnosed by histopathological analysis. The majority of patients with an invasive pulmonary fungal disease were culture-negative. Although culture can clarify the fungal pathogen species, it has low sensitivity. Pathological examination with fungal stains has its advantages in diagnosing fungal disease; therefore, more attention should be paid to the role of pathological examination in the diagnosis of fungal disease.